The efficacy and safety of using the topical medicine with combined action in patients with opportunistic vaginal infections - Vera N. Prilepskaya; Giuldana R. Bairamova; Elena A. Mezhevitinova; Andrei E. Donnikov; Dmitry Yu. Trofimov; Tatyana Yu. Ivanets; Ilia V. Kukes (IP Berlin A.V., 2020)
Relevance.Infections of the lower genital tract are one of the most common reasons for women to visit a gynecologist. According to various authors, among all vulvovaginitis, the highest percentage of patients visiting a doctor is bacterial vaginosis (2050%), vulvovaginal candidiasis (1739%), trichomoniasis (10%) and other genital infections (10%). In the management of patients with infectious processes of the genitals, the choice of the method of therapy is of great importance, which allows not only to influence the microbes-associates, detected in high concentrations in the womans vagina during the initial episode of the disease, but also to prevent the development of relapses. Aim.To evaluate the clinical and laboratory efficacy, adherence and long-term results of benzydamine use in patients with vulvovaginal candidiasis, aerobic vaginitis and bacterial vaginosis Materials and methods.The study included 31 women aged 18 to 49 years, who complained of abundant discharge from the genital tract, itching, burning, dyspareunia. A comprehensive clinical and laboratory examination was carried out, including the collection of anamnestic data, general and special gynecological examination, microscopy of vaginal smears, KOH test, determination of the pH of the vaginal environment, assessment of vaginal microbiocenosis by quantitative PCR in real time. All patients were prescribed benzydamine hydrochloride, which was used as monotherapy in the form of a vaginal solution according to the recommended treatment regimen specified in the instructions for medical use of the drug TantumRosa 1 (irrigation 2 times a day for 10 days). Results.In 1219 days after beginning treatment, 25 (80.6%) of 31 patients with laboratory signs of vaginal microflora alterations showed restoration of the normal vaginal biocenosis laboratory parameters. Of them, 8 patients initially had dysbiosis, 12 patients yeast-like fungi, 4 patients aerobic vaginitis and 1 patient a combination of dysbiosis and fungi. Herewith, all patients also noted clinical signs of improvement. In 1219 days after beginning treatment, 6 (1.4%) of 31 patients with laboratory signs of vaginal biocenosis alterations had unsatisfactory laboratory parameters; that is vaginal biocenosis alterations (a decrease in Lactobacillus spp. percentage). At the same time, there were no clinical signs of pronounced inflammation such as pathological discharge, hyperemia, vaginal swelling. Conclusion.Benzydamine hydrochloride can be widely used in gynecological practice due to its combined effects on inflammation of the vagina, good clinical and microbiological results. It is important to note that additional therapy with drugs which contain lactobacilli is required only in 19.4% of cases. The clinical and laboratory effectiveness of benzydamine hydrochloride (TantumRosa) was 96.8%, since the relapse rate after 3060 days of the study did not exceed 3.2%.